Učenje slovenskega jezika in ohranjanje slovenske kulture v Bosni in Hercegovini - Kern, Boris (Dve domovini, 2025)
Relations between the Republic of Slovenia and Bosnia and Herzegovina are close, also due to the rich history of migration between the two countries. This article focuses on the collaborative aspect between various institutions and organizations involved in teaching the Slovenian language and/or preserving Slovenian culture in Bosnia and Herzegovina. Particular attention is paid to the inclusion of higher education, as the teaching of Slovenian at this level came to a halt for nearly two decades following the dissolution of the Socialist Federal Republic of Yugoslavia.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; dopolnilni pouk slovenščine; lectureships of Slovenian language abroad; lektorati slovenščine v tujini; Slovenian cultural associations; Slovenian emigrants; Slovenian language; slovenska društva; slovenski izseljenci; slovenski jezik; supplementary classes